Gentoo penguins (Pygoscelis papua) react to underwater sounds. Issue 2 (26th February 2020) - Sørensen, K.; Neumann, C.; Dähne, M.; Hansen, K. A.; Wahlberg, M.
Abstract : Marine mammals and diving birds face several physiological challenges under water, affecting their thermoregulation and locomotion as well as their sensory systems. Therefore, marine mammals have modified ears for improved underwater hearing. Underwater hearing in birds has been studied in a few species, but for the record-holding divers, such as penguins, there are no detailed data. We played underwater noise bursts to gentoo penguins ( Pygoscelis papua ) in a large tank at received sound pressure levels between 100 and 120 dB re 1 µPa RMS. The penguins showed a graded reaction to the noise bursts, ranging from no reactions at 100 dB to strong reactions in more than 60% of the playbacks at 120 dB re 1 µPa. The responses were always directed away from the sound source. The fact that penguins can detect and react to underwater stimuli may indicate that they make use of sound stimuli for orientation and prey detection during dives. Further, it suggests that penguins may be sensitive to anthropogenic noise, like many species of marine mammals.